'A cultural education toward pain': The case of Louise DeSalvo. Issue 4 (1st December 2022) - Capalbo, Giuseppe
Abstract : This article analyses the inscription of pain in the memoirs and theoretical writings of Louise DeSalvo, a leading figure in the Italian American literary community who contracted a mysterious disease – later identified as asthma – as a form of post-traumatic stress disorder (PTSD). It argues that, in the context of breathlessness, the act of 'writing through' intertextual references to canonical literature allows the writer to 'find the ultimate expression of the asthmatic life' (DeSalvo 1997 : 85). By taking into account her theoretical background, the article explores her memoirs as 'palimpsests of traumatic memory' and reveals that, as her work focuses on the brain as much as the body in the complex experience of dyspnoea, it aligns with the latest clinical and medical-humanities research on breathing and breathlessness.